Synthesis and characterisation of zeolite-A and Zn-exchanged zeolite-A based on natural aluminosilicates and their potential applications. Issue 1 (1st January 2018) - Nyankson, Emmanuel; Efavi, Johnson Kwame; Yaya, Abu; Manu, Gloria; Asare, Kingsford; Daafuor, Joseph; Abrokwah, Richard Yeboah
Abstract: Zeolites have been hydrothermally synthesized using alumina and silica based deposits (kaolin, bauxite, silica and feldspar) sampled from three regions in Ghana and the chemical compositions of the zeolites varied by batch formulations. The as-synthesized zeolites were characterized using X-ray Diffraction, Fourier Transform Infra-Red and Porosimetry techniques. The morphology and elemental compositions were examined using Scanning Electron Microscopy and energy dispersive X-ray spectroscopy (EDX). The results indicate that zeolite A was formed with a cubic structure and structural variations depending on the batch formulations. By increasing the silica content (Si/Al ratio) through batch formulations, the crystallite sizes of zeolites increased forming Zeolite A with LTA structure and Zeolite A (K-exchanged dehydrated). Samples with higher alumina content produced Zeolite A (Hydrated), Zeolite-Na and Zeolite A (Na, Dehydrated) with lower crystallite sizes. The zeolite synthesized was then used in the synthesis of zinc exchanged Zeolite A (Zn-zeolite A). EDX analysis confirmed a complete exchange of Na in the Zeolite framework with Zn and the feasibility as an adsorbent for methylene blue tested. The synthesized Zn-exchanged Zeolite A showed strong adsorption for methylene blue dye. The adsorption kinetics of the MB onto Zn-exchanged Zeolite A was observed to follow pseudo-second-order model. Freundlich model better described the interaction among adsorbate molecules onto the Zn-exchanged Zeolite A adsorbent, suggesting a multilayer distribution of adsorbate molecules with some level of interaction between adsorbed molecules. The regeneration capacity of the adsorbent was low and calculated to be about 48% at pH of 12.